2003
DOI: 10.1021/jp0270248
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of Rate Constants for Tb3+(5D3) Cross Relaxation in Symmetric Tb3+ Pairs in Tb-Doped CsCdBr3, CsMgBr3, CsMgCl3

Abstract: Microscopic rate constants for Tb(5D3) cross relaxation have been determined as a function of temperature in symmetrical Tb3+−Tb3+ pairs in CsCdBr3, CsMgBr3 and CsMgCl3. The temperature dependence and maximum efficiency of cross relaxation is very different in the three hosts, despite the fact that the energy-level structures and luminescence spectra are quite similar. The difference in cross relaxation behavior in the three systems is due to the fact that the degree of resonance is the dominant factor in dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 63 publications
1
22
0
Order By: Relevance
“…(5) is actually a cross relaxation between the à Eu 2þ and ½Eu 2þ þ à e centers. Cross relaxation takes place via the pairs of the energy donors and acceptors existing in the crystal lattices [7] or the energy migration among the donors [8,9]. The latter is believed to be the case because of the overlap between the excitation and emission spectra of Eu 2+ in SrAl 2 O 4 , as shown in Fig.…”
Section: Article In Pressmentioning
confidence: 99%
“…(5) is actually a cross relaxation between the à Eu 2þ and ½Eu 2þ þ à e centers. Cross relaxation takes place via the pairs of the energy donors and acceptors existing in the crystal lattices [7] or the energy migration among the donors [8,9]. The latter is believed to be the case because of the overlap between the excitation and emission spectra of Eu 2+ in SrAl 2 O 4 , as shown in Fig.…”
Section: Article In Pressmentioning
confidence: 99%
“…Therefore, Tb 3+ activated phosphors with tunable emitting colors can be achieved by choosing a low phonon frequency host. We summarize the reported tunable color luminescence in Tb 3+ doped materials [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41], as shown in Table 1. The approximate values of the phonon frequency in some oxides containing ionic complexes and fluoride compounds have been reported, such as borates ($1300 cm À1 ), phosphates ($1200 cm À1 ), silicates ($1050 cm À1 ), tungstates ($900 cm À1 ), aluminates ($850 cm À1 ), fluorides ($450 cm À1 ).…”
Section: Structural and Morphology Characteristicsmentioning
confidence: 99%
“…Fig. 3 shows the PL spectra of KY 3 F 10 :Tb 3+ with different Tb 3+ concentrations under 218 nm excitation, where the intensities of the blue Halide compounds Ca 6 Ln 2 Na 2 (PO 4 ) 6 F 2 (Ln = Gd, La) [34] Rb 2 KInF 6 [35] b-NaYF 4 [36] K 2 YF 5 [37] ZBLAN [38] a-GdOF [39] CsMgCl 3 [40] CsMgBr 3 [40] CsCdBr 3 [40,41] emission originating from 5 D 3 are normalized. At low concentrations of Tb 3+ , the blue emissions from the 5 D 3 level are dominant in the fluorescence spectra, indicating that the 5 D 3 level is effectively populated when excited at 4f 7 5d configuration.…”
Section: Structural and Morphology Characteristicsmentioning
confidence: 99%
“…The energy transfer mechanism was deduced to be electric dipole-electric dipole (ED-ED) for Y 3 Al 5 O 12 :Tb 3+ [12], a-GdOF [13] and for LiYF 4 :Tb 3+ above 70 K [10], but electric quadrupole-electric quadrupole (EQ-EQ) at 4.2 K for LiYF 4 :Tb 3+ . From a detailed consideration of the crystal field energy levels for the systems CsCdBr 3 , CsMgBr 3 and CsMgCl 3 doped with Tb 3+ at a C 3v site [14], it was concluded that the cross-relaxation mechanism involved resonant 'hot' transitions and that phonon-assisted processes were not important. As mentioned above, since dipole-dipole processes are forbidden for Cs 2 NaYF 6 :Tb 3+ unless they are phonon-assisted, it was of interest to investigate the 5 D 3 concentration quenching in this system in view of the above conclusions.…”
Section: Introductionmentioning
confidence: 99%